Study on the perception of staff and students of a university on community pharmacy practice in Ipoh, Perak, Malaysia - Mathews, Allan; Azad, Abul Kalam; Abbas, Syed A.; Che Rose, Farid Z.; Helal Uddin, A.B.M. (Wolters Kluwer - Medknow, 2018)
Background: In Malaysia, community pharmacies play an important and vital role in both urban and rural areas with approximately 30% of 12,000 registered pharmacists with annual retention certificate practicing in community pharmacies. The main objective of this study was to find the perception of respondents on the value and necessity of pharmacists. Materials and Methods: The questionnaire was divided into two sections: the first section assessed the visits to community pharmacies, purpose, interaction with pharmacy staffs, professional fee, and improvements to pharmacy practices; the second section evaluated the characteristics of respondents including an e-consent form. Data were analyzed using the Statistical Package for the Social Sciences software (version 11.5). Results: The highest number of respondents (66.1%) consulted with the pharmacists for cough and cold, 33.1% for gastric and stomach ailments, and 28.9% for diarrhea and constipation. Only 34% of cases were handled by the pharmacists, whereas 52.1% by the sales assistant. Approximately 88.5% showed satisfaction with the counseling provided. A total of 46.3% did not know whom they dealt with, whereas 51.2% wanted personal attention of the pharmacists instead of the sales assistants. However, 66.9% of respondents preferred to a private consultation room. Records of only 32.2% of respondents were secured by the pharmacies, whereas 42.1% showed interest to pay a professional fee. Moreover, 83.3% agreed the fee of RM5 only, whereas 20.8% agreed to RM10. Among the respondents, majority agreed to pay a fee willingly, but approximately 30% stayed neutral. Conclusion: There is a need for the community pharmacists to play vital roles firsthand at the front desk to serve the patients professionally instead of handing over the responsibilities to the sales assistant.